Research on Teaching Idea Innovation of University Physical Education Teachers - Huang, Jin; Wang, Shaojie; Zhu, Jun; Cai, Jiao; Jiang, Bo (Quality in Sport, 2024)
This study takes the teaching reform concept of university PE teachers in the new era as the research object, and uses the literature method, logical analysis method and inductive deduction method to deeply analyze the development opportunity and realistic bottleneck of the teaching innovation concept of university PE teachers. The research shows that the teaching innovation concept of university PE teachers faces new challenges, and the generalization of education consciousness and the motivation of concept innovation of university PE teachers are insufficient. "Cultivating morality and cultivating people" as the basic task of education, the author puts forward the concept of "moral education first" in the innovation of teaching concept of physical education teachers in universities. Construct the evaluation system of "cultivating virtue" and "cultivating body"; To construct a new model of post-service education for physical education teachers in universities, and establish a new standard for the evaluation of professional titles of physical education teachers in universities; The new model of cultivating multi-disciplinary high quality sports talents and the concept of PE teachers' education should be integrated with aesthetic education. The aim is to provide theoretical reference for the timely updating of the teaching concept of university PE teachers under the background of the new era and optimizing the classified development of university PE teachers.